Identification of cover crops for the semiarid savanna zone of West Africa - Carsky, R.J.; Ndikawa, R. (1998)
Leguminous cover crops may be an appropriate component of sustainable food-production systems in the semi-arids avannas of West and Central Africa- A set of erect and spreading legumes was observed for adaptation D to a semi-arid climate (700-900 mm annual rainfall), without fertilizer application, on three soil t ?es in northern Cameroon- Mucuna pwiens genetically reached l00o/o ground cover 60-90 d after planting, where is Canaralid ensi form is rarely reached1 0070g round cover, Two C. enst form is accession so, ne erect and one spreading differed in their ability to covert the soil surface. Maximum foliage dry matter (DM) exceeded that of the locally adapted spread it rg cowpea in most cases. Foliage DM of M. pruriens, C. ensiformis, Clotalaria ochroleuca, and Cajanus cajan genetally exceeded 4 that all but the most degraded site. At the degraded site, the erect Censi-onnrs accession produced 5 -7 t DM htt. Canavaliae nsifotms grcw longer into the dry season and maintained high ermoisture content, suggesting some drought resistatnce because of strong winds during the dry season and trampling during seed collection, foliage DM less than about 4 t ha I did not persist through the dry season. Uncontrolled cattle grazing was another threat to persistence of mulch though the dry season.